Aufbruch in eine Welt jenseits von p < 0,05 - Vielitz, Arne (manuelletherapie, 2020)
Wasserstein RL, Schirm AL, Lazar NA. Moving to a World Beyond “p < 0.05”. American Statistician 2019; 73 (sup1): 1–19. doi: 10.1080/00031305.2019.1583913